2016
DOI: 10.1515/acve-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteriosis in Pigs – An Underrated Threat

Abstract: Although Mycobacterium avium subspecies are generally not considered food pathogens, the infections caused by these particular nontuberculous mycobacteria (NTM) can represent a serious threat to immunocompromised population. Additionally, infections with a member of Mycobacterium Avium Compex (MAC) can affect the effi ciency of BCG vaccines used for the humans. In infected animals, M. avium may be present in different tissues without apparent clinical symptoms and macroscopic lesions. Veterinary meat inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…Over the last few decades, lung lesions have represented one of the most important health and welfare issues in intensive pig farming worldwide (Flesja and Ulvesaeter, 1980;Ujvári et al, 2015;Palzer et al, 2015;Sárközi et al, 2015;Čobanović et al, 2016a;Lukač et al, 2016;Polaček and Aleksić-Kovačević, 2016). They cause significant financial losses to the pig industry, arising from reduced growth rate and feed conversion, high morbidity and mortality, increased medication costs, condemnation of offal and carcasses, and lower carcass quality (Ostanello et al, 2007;Becskei et al, 2010;Fraile et al, 2010;Toplak et al, 2012;Čobanović et al, 2015;Štukelj et al, 2015;Szeredi et al, 2015).…”
mentioning
confidence: 99%
“…Over the last few decades, lung lesions have represented one of the most important health and welfare issues in intensive pig farming worldwide (Flesja and Ulvesaeter, 1980;Ujvári et al, 2015;Palzer et al, 2015;Sárközi et al, 2015;Čobanović et al, 2016a;Lukač et al, 2016;Polaček and Aleksić-Kovačević, 2016). They cause significant financial losses to the pig industry, arising from reduced growth rate and feed conversion, high morbidity and mortality, increased medication costs, condemnation of offal and carcasses, and lower carcass quality (Ostanello et al, 2007;Becskei et al, 2010;Fraile et al, 2010;Toplak et al, 2012;Čobanović et al, 2015;Štukelj et al, 2015;Szeredi et al, 2015).…”
mentioning
confidence: 99%
“…Актуальність теми. Проблемі зв'язку розвитку патологій людей та тварин із інфікуванням нетуберкульозними мікобактеріями, зокрема, Mycobacterium avium complex, присвячена численна кількість публікацій (Crilly, Ayeh, & Karakousis, 2021;Zhurylo, Barbova, & Cladkova, 2020;Ratnatunga et al, 2020;Azar, Zimbric, Shedden, & Caverly, 2019;Kreutz-Rodrigues, & Bakri, 2019;Schiff et al, 2019;Krajewska-Wędzina, Dąbrowska, Augustynowicz-Kopeć, Weiner, & Szulowski, 2019;Lande et al, 2019;Auguste, Patel, & Siemieniuk, 2018;Honda, Virdi, & Chan, 2018;Lande, George, & Plush, 2018;Hwang, Kim, Jo, & Shim, 2017;Nishiuchi, Iwamoto, & Maruyama, 2017;Srivastava, Dahiya, Singh, & Kulshreshtha, 2017;Polaček, & Aleksić-Kovačević, 2016). У той же час, нові складні випадки коінфекції Mycobacterium tuberculosis/Mycobacterium avium complex (чи інших нетипових мікобактерій та вірусу імунодефіциту людини), вимагають удосконалення підходів щодо їх діагностики та трактування патогенезу (Santos-Pereira, Magalhгes, Arajo, & Osуrio, 2021;Sharma, Latawa, Wanchu, & Verma, 2021;Bazzi, Abulhamayel, Rabaan, & Al-Tawfiq, 2020;Abdeldaim, Svensson, Blomberg, & Herrmann, 2016;Rocchetti, Silbert, Gostnell, Kubasek, & Widen, 2016;Danelishvili et al, 2015).…”
Section: вступunclassified
“…Calcification of tubercles, inflamed lymph nodes (lymphadenitis) and tuberculosis-like granulomas are the most common features of mycobacteriosis in pigs ( Agdestein et al, 2014 ). Mycobacterial infection in pigs is mainly asymptomatic; as such, lesions are mostly detected during slaughter ( Polaček and Aleksić-Kovačević, 2016 ). Some studies have reported clinical signs-like abortion and wasting due to MAH in pigs ( Wellenberg et al, 2010 ; Eisenberg et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have reported infection of pigs with MAC and other mycobacteria, to present no detectable clinical signs and the granuloma appear very minute (Agdestein et al, 2011(Agdestein et al, , 2012. As such, pigs infected with mycobacteria can be missed during inspection at slaughter and the meat may enter the human food chain posing a serious public health threat especially to the immuno-compromised individuals, children, and the elderly (Polaček and Aleksić-Kovačević, 2016). Despite these findings, meat inspection is still an important practice for identification of pig mycobacterial infections in order to mitigate the risk of human exposure.…”
Section: Introductionmentioning
confidence: 99%